Teachers’ Perception of the Implementation of Quizizz as an Alternative Teaching Media - Rizqi Febrian Pramudita; Enik Rukiati (P3M Politeknik Negeri Jember, 2022)
Since the emergence of Covid-19, almost every sector of human life on this planet has been altered, including education. This also brought an impact on Politeknik Negeri Jember . Until the first half of the even Semester of the Academic Year 2021/2022, learning activities were carried out virtually through two main media, namely the Learning Management System (LMS) and video conferencing application such as Zoom. Unfortunately, during the period, the condition led to the lack of interactive learning by the lecturers of English study program on virtual classroom. To deal with this, one of the solutions was the use of Quizizz as a learning app for lecturers in the English study program of Language, Communication and Tourism department of Politeknik Negeri Jember. This study focused on investigating teachers’ perception regarding their experience in using the application which was relatively new for many of them. The study involved 21 lecturers of English study program of Politeknik Negeri Jember as the participants of Quizizz short workshop. The findings indicated that participants were enthusiast of having teaching learning activities using Quizizz. The participants enjoyed Quizizz and thought it was exciting, interesting, motivating, and enjoyable, especially while doing the online quiz. In addition, the results of quiz that accomplished by them can be seen and evaluated since it was recorded on teacher’s database of Quizizz application.